Báo cáo tổng hợp giải trình, tiếp thu ý kiến góp ý về dự thảo Luật Dầu khí (sửa đổi) - Bộ Công thương (2022)
Toàn văn Báo cáo tổng hợp giải trình, tiếp thu ý kiến góp ý về dự thảo Luật Dầu khí (sửa đổi)